2022
DOI: 10.1021/acsami.2c11140
|View full text |Cite
|
Sign up to set email alerts
|

Type-II CuFe2O4/Graphitic Carbon Nitride Heterojunctions for High-Efficiency Photocatalytic and Electrocatalytic Hydrogen Generation

Abstract: Solar water splitting has emerged as an urgent imperative as hydrogen emerges as an increasingly important form of energy storage. g-C3N4 is an ideal candidate for photocatalytic water splitting as a result of the excellent alignment of its band edges with water redox potentials. To mitigate electron–hole recombination that has limited the performance of g-C3N4, we have developed a semiconductor heterostructure of g-C3N4 with CuFe2O4 nanoparticles (NPs) as a highly efficient photocatalyst. Visible-light-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 63 publications
0
50
0
Order By: Relevance
“…[83] The synergistic effects enhance the photocatalytic activity by overcoming aforementioned disadvantages and thus, proven very efficient for hydrogen generation by utilizing oxide based heterostructured photocatalysts. [84]…”
Section: Photocatalytic H 2 Generationmentioning
confidence: 99%
“…[83] The synergistic effects enhance the photocatalytic activity by overcoming aforementioned disadvantages and thus, proven very efficient for hydrogen generation by utilizing oxide based heterostructured photocatalysts. [84]…”
Section: Photocatalytic H 2 Generationmentioning
confidence: 99%
“…Enhancing the photochemical response of photocatalysts is basically reliant on four factors that are (a) inhibiting the recombination of photo-induced electron-hole pairs, (b) tailoring the band gap of photocatalysts in the visible light region, (c) suitable catalytic support acting as a co-catalyst and (d) a higher specific surface area as it provides more adsorption sites [3,14,41,92]. To improve the photocatalytic activity, an efficient photocatalytic system should possess durable photo-induced charge carriers, fewer charge-capturing sites and a suitable band gap [93][94][95][96].…”
Section: Photocatalytic H 2 Productionmentioning
confidence: 99%
“…One of the most economical and efficient ways of H 2 production is overall water splitting (OWS) [41]. OWS is a chemical approach that enables H 2 evolution by breaking the water into its elemental composition, hydrogen and oxygen [42].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the protection against microbial corrosion, the addition of antibacterial components to the protective paints or coatings has been commonly used to achieve antifouling and antibacterial effects [ 19 ]. Although many heavy metals and rare earth elements, such as Cu, Ag, Ce, La, etc., have a strong bactericidal effect [ 20 , 21 , 22 ], their adverse effects on the environment need to be considered [ 23 ]. It is reported that some semiconductors can be also used for photocatalytic sterilization and antifouling, which is correlated with the generation of reactive oxygen species (ROS, such as superoxide radicals •O 2 − and hydroxyl radicals •OH) under irradiation and their inhibition to the growth of bacteria [ 24 ].…”
Section: Introductionmentioning
confidence: 99%